COMPARATIVE STUDY OF NONGSHIM INSTANT NOODLE PACKAGING DESIGN IN SOUTH KOREA AND IN INDONESIA - Natadjaja, Listia (Nirmana, 2006)
These days due to the global market development, there are many products that are marketed outside the local area. I found that there are differences between local and export design in Nongshim instant noodle packaging, marketed in South Korea and in Indonesia. This study, discusses the differences between packaging design elements of the famous instant noodle brand in South Korea. Hopefully, through this study, we can have a description of what kind of design elements should be kept and what kind of information should be added or changed for the export product. Abstract in Bahasa Indonesia: Saat ini dikarenakan perkembangan pasar global, banyak produk yang dipasarkan di luar area lokal. Penulis menemukan perbedaan yang menarik anmtara desain lokal dan desain yang diperuntukan untuk eksport pada kemasan mie instant merek Nohngshim yang dipasarkan di Korea Selatan dan di Indonesia. Pada studi ini, penulis ingin membahas perbedaan apa sajakah yang terdapat pada elemen-elemen desain kemasan sebuah merek mie instant yang terkenal di Korea Selatan. Diharapkan melalui studi ini, kita bisa mendapatkan sebuah gambaran elemen-elemen desain apa saja yang harus dipertahankan dan informasi apa saja yang harus ditambahkan atau dirubah untuk produk ekspor. Kata kunci: mie instant Nongshim, Korea Selatan, Indonesia, desain kemasan.